Analysis of morbidity with poisonings with ethanol and surrogate alcohols in irkutsk region between 2010 and 2017 - E. I. Loskutnikova; A. U. Gil; I. N. Alekhin; R. A. Khalfin (Сеченовский вестник, 2019)
Aim. Poisonings with ethanol and surrogate alcohols are preventable causes of morbidity and mortality posing a serious threat to population health. The aim of the study was to analyze the dynamics of the incidence of acute poisoning with ethyl and surrogate alcohols in the Irkutsk region for the period from 2010 to 2017, and to discuss it in the context of the regional and federal policy aimed at regulation of the alcohol - containing products. Materials and methods. The data of the statistical reporting form No. 12-15 “Information on the results of toxicological monitoring” in the Irkutsk region for the period from 2010 to 2017, the data of the Federal State Statistics Service RosStat on the incidence of acute chemical poisoning, and on incidence of acute poisoning with ethyl alcohol and surrogate alcohols were analyzed. Subsequent interpretation of the results in the context of the regional and federal alcohol control policy has been performed. Results. In the Irkutsk region, during the analyzed period of time there was observed a high incidence of acute poisonings with ethanol and surrogate alcohols with territorial diﬀerences within the region, and with positive dynamics of reduction of incidence by 38.7% in 2017 in comparison to 2010. Poisonings with ethanol occupy a leading place in the structure of the incidence in comparison with poisoning with other alcohols. The Irkutsk region was ranked 9th among all other subjects of the Russian Federation in 2017 by level of morbidity with alcohol poisonings. Among all cases of poisonings the proportion of the adult working age population was 89.1%, males - 77%, and unemployed population - 57.8%, which suggests that these categories of population are under the highest risk of acute poisoning with ethanol and surrogate alcohols. Conclusion. Strengthening control over the illegal distribution of ethyl alcohol and alcohol - containing products, especially in the territories situated along the Federal highways is seen as a priority area for action. Control of distribution of alcohols between 2010 and 2017 on the territory of the Irkutsk region allowed reducing incidence of poisonings by 38.7%. To maintain the positive dynamics of reducing morbidity and mortality from acute poisoning of alcohol etiology, to preserve the labor potential of the population of the Irkutsk region, it is necessary to further strengthen and reinforce control measures at the regional level.